2012
DOI: 10.1097/nnd.0b013e318240a65a
|View full text |Cite
|
Sign up to set email alerts
|

Professional Nursing Burnout and Irrational Thinking

Abstract: This expanded (n = 648) replication study examines job-related burnout in practicing nurses in relation to five maladaptive thinking patterns at eight northeast Florida hospitals. Data supported the hypothesis that maladaptive thinking patterns may be related to nurses' burnout thoughts and behaviors. The focus of this research spotlights the individual nurse's thoughts, emotions, and actions and suggests that these burnout tendencies can be mitigated if not changed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…Only one study has directly examined the relationship between irrational beliefs and mental health outcomes, which revealed that irrational beliefs predicted increases in physical and emotional exhaustion (a dimension of burnout) in Gaelic football athletes over an 8-week period ( Turner and Moore, 2015 ). This finding is inline with past research outside of sport linking irrational beliefs to greater burnout (e.g., Balevre et al, 2012 ). But clearly more longitudinal, large-scale, studies are required in order to investigate fully the relationships between irrational beliefs and dysfunctional responses, especially focusing on athletes.…”
Section: Moving the Area Forwardsupporting
confidence: 91%
“…Only one study has directly examined the relationship between irrational beliefs and mental health outcomes, which revealed that irrational beliefs predicted increases in physical and emotional exhaustion (a dimension of burnout) in Gaelic football athletes over an 8-week period ( Turner and Moore, 2015 ). This finding is inline with past research outside of sport linking irrational beliefs to greater burnout (e.g., Balevre et al, 2012 ). But clearly more longitudinal, large-scale, studies are required in order to investigate fully the relationships between irrational beliefs and dysfunctional responses, especially focusing on athletes.…”
Section: Moving the Area Forwardsupporting
confidence: 91%
“…[6][7][8] Crucially, irrational beliefs can build maladaptive cognitive patterns which lead to professional burnout. 9,10 Limitations of the current study, include a small sample size and lack of demographic data which meant relationships between various factors could not be investigated. However, the REAEI program appears to produce positive results and certainly warrants further investigation in a larger study.…”
Section: Discussionmentioning
confidence: 95%
“…4 Burnout symptoms are considered to result primarily from irrational beliefs, [6][7] Indeed, there is evidence to show that irrational beliefs significantly predict burnout behaviors, 6 and maladaptive thinking patterns correlate with burnout behaviors. [8][9][10] Therefore, rational-emotive behaviour therapy (REBT) programmes may be of use in helping to reduce burnout symptoms. 6 One study found that a rational-emotive health education intervention (REHEI) based on REBT principles was significantly effective in stress management and irrational beliefs among college teachers.…”
Section: Introductionmentioning
confidence: 99%
“…[62][63][64][65] These consequences can lead to inadequate staffing, which in turn, is linked to unfavorable patient outcomes such as hospital-acquired infections. 66 Lingering effects of providers' moral distress can lead to moral desensitization, 50 harmful workplace climates, 23 and suffering of patients and their families. 26 The health system itself is financially affected when moral distress drives nurses and other providers to decrease their work engagement and productivity.…”
Section: 50mentioning
confidence: 99%